Discrete energy levels of Caroli-de Gennes-Matricon states in quantum limit in FeTe0.55Se0.45 - Mingyang Chen (Nature Portfolio, 2018)
Despite predicted decades ago, the discrete Caroli-de Gennes-Matricon states are difficult to observe. Here, Chen et al. observe discrete states appearing near zero bias at the vortex center of FeTe0.55Se0.45, strongly suggesting a Caroli-de Gennes-Matricon state.